Uzbekistan's global vision: advancing human dignity, regional cooperation, and international solidarity - Abd Rahman, Shukran; Islamov, Shahzod (Human Assistance & Development International Inc. (HADI Inc.), 2025)
The dynamic changes of the modern world have compelled many nations to adopt renewed perspectives on human livelihood and the future of global development. Uzbekistan is no exception.Like other countries, it faces the challenges of a rapidly changing and increasingly complex world. This global scenario is shaped by multiple factors which include intensified conflicts and wars among nations, widening technological and social inequalities, deepening economic and humanitarian crises, and the weakening of international institutions meant to address such issues. At the 80th Session of the United Nations General Assembly, the President of the Republic of Uzbekistan, Shavkat Mirziyoyev, outlined Uzbekistan's priorities and achievements in navigating this reality while affirming the vision of a New Uzbekistan. His address reflected both national development goals and a global outlook grounded in solidarity, peace, and human dignity.